Detection of corneal arcus using rubber sheet and machine learning methods - Ramlee, Ridza Azri (2019)
Corneal Arcus (CA) is a sediment accumulation that occurs by the production of lipid (i.e. cholesterol) in the ocular eye. It is associated with hyperlipidemia caused by abnormal lipids present in the blood vessels. It occurs around the cornea with 0.3 - 1 mm wide in the iris-sclera region. The appearance of it looks like a yellowish-white ring around the cornea. This condition often occurs among older people, but in the case with young people, it is risky which associated to heart problems or stroke. In a health examination, usually an ophthalmologist or doctor who finds the patient has a CA sign, will ask them to do further treatment such as blood test. This is to ensure cholesterol (lipid) in their blood is normal or not. This procedure requires a small amount of blood taken from the blood vessels in the patient's arms. It is slightly painful, requires cost and time, besides the patient should fast for 12 hours before the test can be done.